Impact of COVID-2019 on stroke services in China: survey from the Chinese Stroke Association. Issue 4 (28th September 2020) - Wang, Xia; Ouyang, Menglu; Carcel, Cheryl; Chen, Chen; Sun, Lingli; Yang, Jie; Zhang, Yao; Chen, Guofang; You, Shoujiang; Cao, Yongjun; Ma, Lu; Hu, Xin; et al.
Abstract : Background: The COVID-19 pandemic and physical distancing guidelines have compelled stroke practices worldwide to reshape their delivery of care significantly. We aimed to illustrate how the stroke services were interrupted during the pandemic in China. Methods: A 61-item questionnaire designed on Wenjuanxing Form was completed by doctors or nurses who were involved in treating patients with stroke from 1 February to 31 March 2020. Results: A total of 415 respondents completed the online survey after informed consent was obtained. Of the respondents, 37.8%, 35.2% and 27.0% were from mild, moderate and severe epidemic areas, respectively. Overall, the proportion of severe impact (reduction >50%) on the admission of transient ischaemic stroke, acute ischaemic stroke (AIS) and intracerebral haemorrhage (ICH) was 45.0%, 32.0% and 27.5%, respectively. Those numbers were 36.9%, 27.9% and 22.3%; 36.5%, 22.1% and 22.6%; and 66.4%, 47.5% and 41.1% in mild, moderate and severe epidemic areas, respectively (all p<0.0001). For AIS, thrombolysis was moderate (20%–50% reduction) or severely impacted (>50%), as reported by 54.4% of the respondents, while thrombectomy was 39.3%. These were 44.4%, 26.3%; 44.2%, 39.4%; and 78.2%, 56.5%, in mild, moderate and severe epidemic areas, respectively (all p<0.0001). For patients with acute ICH, 39.8% reported the impact was severe or moderate for those eligible for surgery who had surgery. Those numbers were 27.4%, 39.0% and 58.1% in mild, moderate and severe epidemic areas, respectively. For staff resources, about 20% (overall) to 55% (severe epidemic) of the respondents reported moderate or severe impact on the on-duty doctors and nurses. Conclusion: We found a significant reduction of admission for all types of patients with stroke during the pandemic. Patients were less likely to receive appropriate care, for example, thrombolysis/thrombectomy, after being admitted to the hospital. Stroke service in severe COVID-19 epidemic areas, for example, Wuhan, was much more severely impacted compared with other regions in China.